Integrated comparative metabolomics and network pharmacology approach to uncover the key active ingredients of Polygonati rhizoma and their therapeutic potential for the treatment of Alzheimer’s disease - Wang, Fu; Chen, Hongping; Hu, Yuan; Chen, Lin; Liu, Youping (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) has become a worldwide disease affecting human health and resulting in a heavy economic burden on the healthcare system. Polygonati rhizoma (PR), a kind of traditional Chinese Medicine (TCM), is known to improve learning and memory abilities. However, its AD-treating material basis and their therapeutic potential for the treatment of AD has remained unclear. Therefore, the present study aimed to uncover the key active ingredients of PR and its therapeutic potential for the treatment of AD. First, we used comparative metabolomics to identify the potential key active ingredients in the edible and medicinal PR. Second, network pharmacology was used to decipher the effects and potential targets of key active ingredients in the PR for the treatment of AD, and molecular docking was further used to identify the binding ability of those active ingredients with AD-related target of AChE. The rate of acetylcholinesterase (AChE) inhibition, oxidative stress, neuroprotective effects, and anti-inflammatory activity were assessed in vitro to screen the potential active ingredients in the PR with therapeutic potential against AD. Finally, APPswe/PS1dE9 AD mice were used to screen the therapeutic components in the PR. Seven overlapping up-regulated differential metabolites were identified as the key active ingredients and cafestol, isorhamnetin, and rutin both have AChE inhibitory activity, anti-inflammatory activity, and neuroprotective effects in vitro validation assays. Further in vivo results showed that cafestol, isorhamnetin, and rutin displayed several beneficial effects in AD transgenic mice by reducing the number of Aβ-positive spots and the levels of inflammatory cytokines, inhibiting the AChE activity, and increasing the antioxidant levels. Each compound is involved in a different function in the early stages of AD. In conclusion, our results corroborate the current understanding of the therapeutic effects of PR on AD. In addition, our work demonstrated that the proposed network pharmacology-integrated comparative metabolomics strategy is a powerful way of identifying key active ingredients and mechanisms contributing to the pharmacological effects of TCM.